CO2 Hydrogenation over Copper/ZnO Single‐Atom Catalysts: Water‐Promoted Transient Synthesis of Methanol. (27th October 2022) - Wu, Wenlong; Wang, Yanan; Luo, Lei; Wang, Menglin; Li, Zhongling; Chen, Yue; Wang, Zhiqi; Chai, Jingbo; Cen, Zeyan; Shi, Yongliang; Zhao, Jin; Zeng, Jie; et al.
Abstract: The hydrogenation of CO2 by renewable power‐generated hydrogen offers a promising approach to a sustainable carbon cycle. However, the role of water during CO2 hydrogenation is still under debate. Herein, we demonstrated that either too low or too high contents of water hampered the methanol synthesis over Cu/ZnO based catalysts. For Cu single atoms on ZnO supports, the optimal content of water was 0.11 vol. % under 30 bar (CO2 : H2 =1 : 3) at 170 °C. Upon the introduction of optimal‐content water, the methanol selectivity immediately became 99.1 %, meanwhile the conversion of CO2 underwent a volcano‐type trend with the maximum of 4.9 %. According to mechanistic studies, water acted as a bridge between H atoms and CO2 /intermediates, facilitating the transformation of COOH* and CH2 O*. The enhanced activity induced the generation of more water to react with CO via water‐gas shift reaction, resulting in the increase in methanol selectivity. Abstract : Acting as a bridge for hydrogen atoms during CO2 hydrogenation, water facilitates the transformation of relatively stable intermediates for enhancing the activity which in turn produces more water to react with CO via the water‐gas shift reaction. As a result, the yield of methanol is promoted by a suitable amount of water over Cu single atoms on ZnO supports.